Fly blanky fly - Lewis, Anne Margaret (Harper, 2012)
Preparing for a grand adventure with his beloved blanket at bedtime, a little boy leaps into an imaginative world where he and his blanket zoom on jet planes, fly to the Moon, and swim in the sea before settling down to sleep.